Brand Authenticity as a Mediator of Relationship Between Self-Congruity and Consumer Loyalty - Hidayat, Susilo; Setiawati, Farida Agus (Faculty of Psychology, Universitas Negeri Yogyakarta, 2021)
This study investigates the effect of brand authenticity as a mediator of self-congruity relationships on coffee shops consumer loyalty. Data obtained by cross-sectional method with convenience/accidental sampling through an online survey platform. Four hundred thirty responses (44.4% male) were collected from consumers of various brands of coffee shops located in DIY. The mediation effect hypothesis was tested using a bootstrapping approach and additional analysis of the causal step approach using the Sobel test. Self-congruity and brand authenticity have a positive effect on brand loyalty. There is a partial mediating effect produced by brand authenticity on the relationship between self-congruity and brand loyalty. Consumers' consideration to be loyal to the brand is not only based on the suitability of their self-concept with the brand image/brand users image (self-congruity), but also the brand's authenticity.